(untitled) (Sahel Journal of Life Sciences FUDMA, 2024)
The study uses benthic macroinvertebrates as indicators to assess water quality in the Luhu Mini Dam, Michika, Adamawa State. The study involves the collection of benthic macroinvertebrate samples over six months, utilizing the Van Veen grab method for sampling and preservation in formalin. Upon transportation to the laboratory, the samples were identified and subjected to statistical analysis, including the Shannon and Weiner Index, Margalefâ€™s Index, Simpsonâ€™s diversity Index, and Pielouâ€™s Evenness. The study aims to provide fundamental information on the health of the Luhu Mini Dam and to understand the water quality and pollution status, thereby informing necessary management measures. The distribution and diversity of species across three different stations. A total of 462 individuals representing 20 taxa from 3 phyla were collected. Station 1 yielded 16 taxa and 162 individuals, station 2 had 17 taxa and 201 individuals, and station 3 had 17 taxa and 99 individuals. The diversity indices revealed variation in the number of species across stations, with stations 3 and 2 having the highest number of species, while station 1 had the lowest. The general diversity (H’) was highest at station 3, followed by stations 1 and 2, whereas station 3 also exhibited the highest Evenness index (E). Moreover, the taxa richness index, as calculated by Margalef’s Index (d), peaked at station 3. Simpson’s dominance index showed that Station 2 exhibited the highest dominance, followed by Station 1 and Station 3. These findings provide valuable insights into the distribution and diversity of species across different biotopes.